ANALISIS PENETAPAN TARIF AGEN BRILINK DALAM PERSPEKTIF HUKUM EKONOMI SYARIAH KECAMATAN BELOPA UTARA KABUPATEN LUWU - Sudirman, Putri; Hasibuddin, M; Lawang, Hasanna; Raehana, Syarifa; Jamaluddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Belopa Utara District, Luwu Regency, and to examine its conformity with the perspective of Islamic economic law. This research uses a field research method with a qualitative approach and a normative sociological approach. The data sources consist of primary data obtained through interviews with BRIlink agents and customers, as well as secondary data from books, journals, and other supporting documents. Data collection techniques include observation, interviews, and documentation, while data analysis is conducted using descriptive qualitative methods through data reduction, data presentation, and conclusion drawing. The results show that the tariff determination system of BRIlink agents in Belopa Utara is not standardized by PT Bank Rakyat Indonesia (Persero) Tbk, but is determined independently by each agent based on operational costs, location distance, and marketing strategies. This leads to variations in tariffs among agents. In terms of service, BRIlink provides convenience for the community in conducting financial transactions; however, tariff transparency is still not optimal. From the perspective of Islamic economic law, the practice of tariff determination is permissible as it represents a service fee (ujrah) in an ijarah contract, as long as it adheres to the principles of justice, transparency, and public benefit. However, significant tariff differences and lack of transparency may lead to elements of gharar (uncertainty) and perceived injustice. Therefore, increased transparency and supervision are needed to ensure that tariff practices align with Islamic economic principles.